Structural Bridge Engineering - Shahidan, Shahiron; Niza Mokhatar, Shahrul; Haziman Wan Ibrahim, Mohd; Jamaluddin, Norwati; Mohd Jaini, Zainorizuan; Ali, Noorwirdawati (IntechOpen, 2016)
There are many books on preliminary studies and research in bridge design as well as basic knowledge on bridge engineering, but most books supply the needs of practicing engineers who may have problems in estimating, designing or constructing suspension bridges. Therefore, this book is intended to serve as a source of information for problems related to bridge engineering including sustainable bridge development, traditional approaches and recent advances in highway bridge traffic loading, aesthetic analysis issues in designing a new bridge, applications of various methods for the dissipation of seismic energy for bridges, new technologies of bridge design as well as structural identification of bridges using non-destructive experimental measurement tests.